Digital Marketing Pengembangan Mutu Varian Dodol Tenjo: Study Dodol Tenjo Cap Boga Rasa dan Dodol Tenjo Cap Madu - Pujia, Dede Puspa; Susilowati; Brotosakti, Anton; Sumardi, Sumardi; Riyanto, Slamet (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This Community Service Activity aims to support the existence of native Tenjo MSMEs which operate in the culinary sector, namely dodol. Currently, technological developments are increasingly sophisticated, which requires all business actors to participate in technological developments to maintain their businesses, including Dodol Tenjo business actors. Due to existing technological developments, Dodol Tenjo business actors can take advantage of digital-based marketing and gradually abandon traditional marketing so that the marketing coverage area becomes wider and can be accessed by anyone and anywhere. So sales of Dodol Tenjo will experience a significant increase. The things that hinder the development of Dodol Tenjo sales that is: the marketing used is still traditional, namely by entrusting the product to shops around Bogor and Tangerang and stagnant business development. Based on this problem, Community Service is carried out by Tangerang Raya University for partners, namely Dodol Tenjo business actors using the method: a) Lecture Method: MSME business actors are given introductory material on digital marketing and discuss the benefits of digital marketing from efficient costs to coverage. unlimited sales area. b) tutorial method: MSME entrepreneurs are given material on how to create an online shop in an application on a cellphone and how to fill in data to be able to make sales online. c) discussion method: MSME business actors are given the opportunity to discuss problems in creating an online shop and operating their online shop in an application.